Sealing of polymeric-microfluidic devices by using high frequency electromagnetic field and screen printing technique - Yussuf, A. A.; Sbarski, I.; Solomon, M.; Tran, N.; Hayes, J. P. (Elsevier B.V., 2007)
This paper describes a new approach of sealing polymeric-microfluidic devices using high frequency electromagnetic field and solvent based polyaniline (PAni). The bonding is achieved by patterning very thin layers of solvent based polyaniline features at the polymer joint interface by using screen printing technique. The absorbed electromagnetic energy is then converted into heat, facilitating a localized thermal bonding of two polymer substrates (PMMA-PMMMA and PC-PC). For a successful outcome, the selection of materials for the substrate and the bonding is important. Polymethymethacrylate (PMMA) and polycarbonate (PC) are chosen, as they are virtually transparent to microwaves. The bonding material is a conductive polymer (polyaniline), which consists basically of conductive solid nano-particles in an organic solvent. A coaxial open-ended probe was used to study the dielectric properties at 2.45 GHz of the polyaniline, PMMA and PC at a range of temperatures up to 120 degrees C. The measurements confirm that a difference in the dielectric loss factor of the polymer substrates and the polyaniline. Microfluidic channels of 100 and 200 mu m wide were fabricated by using lithography technique then prepared a master mold for hot embossing the samples. The sealing was achieved by using a microwave power of 300 W and heating time of 35 and 40 s for PMMA and PC substrates, respectively. The patterned polyaniline structure at the polymer interface was evaluated by using laser scanning confocal microscope (LSCM). Bonding efficiency of the sealed microfluidic channels were evaluated by using techniques such as interface evaluation or cross-sectioning of the sealed devices, peel off test, bond strength and leak test.